2022
DOI: 10.1002/tcr.202200213
|View full text |Cite
|
Sign up to set email alerts
|

Hollow Heterostructured Nanocatalysts for Boosting Electrocatalytic Water Splitting

Abstract: The implementation of electrochemical water splitting demands the development and application of electrocatalysts to overcome sluggish reaction kinetics of hydrogen/oxygen evolution reaction (HER/OER). Hollow nanostructures, particularly for hollow heterostructured nanomaterials can provide multiple solutions to accelerate the HER/OER kinetics owing to their advantageous merit. Herein, the recent advances of hollow heterostructured nanocatalysts and their excellent performance for water splitting are systemati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(38 citation statements)
references
References 136 publications
0
38
0
Order By: Relevance
“…Because of the strong self-assembly ability of 2-MIM and Zn­(NO 3 ) 2 ·6H 2 O, the resultant Ag@ZIF-8 HNWs were completely covered by the ZIF-8 polyhedron (Figure d,e). The XRD pattern of Ag@ZIF-8 HNWs also showed the corresponding characteristic peaks of ZIF-8, which were located at 7.2, 10.3, and 12.6° (Figure S1a). With the subsequent anion-exchange reaction with S 2– , the collected Ag@ZnS retains the HNW-like structure with a rough surface (Figure f) and distinctive crystal phases of Ag and ZnS (Figure S1b).…”
Section: Resultsmentioning
confidence: 94%
“…Because of the strong self-assembly ability of 2-MIM and Zn­(NO 3 ) 2 ·6H 2 O, the resultant Ag@ZIF-8 HNWs were completely covered by the ZIF-8 polyhedron (Figure d,e). The XRD pattern of Ag@ZIF-8 HNWs also showed the corresponding characteristic peaks of ZIF-8, which were located at 7.2, 10.3, and 12.6° (Figure S1a). With the subsequent anion-exchange reaction with S 2– , the collected Ag@ZnS retains the HNW-like structure with a rough surface (Figure f) and distinctive crystal phases of Ag and ZnS (Figure S1b).…”
Section: Resultsmentioning
confidence: 94%
“…These results indicated that Mo doping and Se vacancies can regulate the electronic structure of Co 9 Se 8 @NiSe/NF step by step, which optimized the adsorption energy for oxygenated intermediates and thus promoted the catalytic activity. [48][49][50][51][52] Considering the promising OER performance of Mo-Co 9 Se 8 @NiSe/NF-60, its overall water splitting (OWS) perform-ance was further explored. The equipment was assembled by coupling Mo-Co 9 Se 8 @NiSe/NF-60 with Pt/C to achieve overall water splitting (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3][4][5] Exploiting advanced materials and green technologies, such as water electrolysis to convert sustainable energy into clean and high-density hydrogen, electrocatalytic CO 2 , and N 2 into valueadded products, is currently promising for addressing the above-mentioned issues. [6][7][8][9][10] The key for these crucial energy conversion technologies is electrocatalysts, which can reduce the activation energy of electrochemical reactions to accelerate the reaction process. 11,12 However, most electrocatalysts cannot meet the high requirement for practical applications due to their limited catalytic activity and poor long-term stability under harsh conditions.…”
Section: Introductionmentioning
confidence: 99%